Adipokines in Nonalcoholic Steatohepatitis: From Pathogenesis to Implications in Diagnosis and Therapy - Emmanuel A. Tsochatzis; George V. Papatheodoridis; Athanasios J. Archimandritis (Hindawi Limited, 2009)
Nonalcoholic fatty liver disease (NAFLD) is the hepatic manifestation of the metabolic syndrome and can vary from benign steatosis to end-stage liver disease. The pathogenesis of non-alcoholic steatohepatitis (NASH) is currently thought to involve a multiple-hit process with the first hit being the accumulation of liver fat which is followed by the development of necroinflammation and fibrosis. There is mounting evidence that cytokines secreted from adipose tissue, namely, adipokines, are implicated in the pathogenesis and progression of NAFLD. In the current review, we explore the role of these adipokines, particularly leptin, adiponectin, resistin, tumor necrosis factor-a, and interleukin-6 in NASH, as elucidated in experimental models and clinical practice. We also comment on their potential use as noninvasive markers for differentiating simple fatty liver from NASH as well as on their potential future therapeutic role in patients with NASH.